Comparability and reliability of the positive and negative affect scales in the European Social Survey - Sortheix, Florencia M.; Weber, Wiebke (Frontiers in Psychology, 2023)
This study examined the measurement invariance of the positive and negative affect scales in the European Social Survey (ESS) in 2006 and 2012. We employed Multi-Group Confirmatory Factor Analysis with an estimator for ordinal data, allowing us to test threshold invariance, which had not been previously investigated for these scales. A 3-item measure of Positive Affect and a 5-item measure of Negative Affect showed that configural, threshold and metric (loading) and partial scalar (intercept) invariance held across almost all countries and between the two ESS Rounds. Our results provide cross-cultural validity to a broader measure of negative affect than past research using the ESS and examine these scales across more countries than any past study. Besides providing valuable insights for researchers interested in well-being and the ESS, our study also contributes to the ongoing discussion about diverging analytical choices in invariance testing.